Wave Breaking and Global Existence for the Generalized Periodic Camassa-Holm Equation with the Weak Dissipation - Ying Zhang; Congming Peng (Advances in Mathematical Physics)
In this paper, a family of the weakly dissipative periodic Camassa-Holm type equation cubic and quartic nonlinearities is considered. The precise blow-up scenarios of strong solutions and several conditions on the initial data to guarantee blow-up of the induced solutions are described in detail. Finally, we establish a sufficient condition for global solutions.